Challenge to Business-Changes in India’s Marketing Environment - Masood, Rana Zehra (Indian Journal of Marketing, 2010)
Globalisation, liberalization and privatization, jointly with speedy strides made by information technology, have brought intense competition in every field of action. Indian industry at present is amazed, perplexed and anxious. The marketing complexities have increased, product life cycles have summarized and the market is unstable than ever before. Indian industry is desperately looking for strategy and action plans that would ensure its survival and growth.